Signaling Pathways in Oxidative Stress-Induced Neurodegenerative Diseases: A Review of Phytochemical Therapeutic Interventions - Zahra Sebghatollahi; Ruchika Yogesh; Neelima Mahato; Vijay Kumar; Yugal Kishore Mohanta; Kwang-Hyun Baek; Awdhesh Kumar Mishra (Antioxidants)
Oxidative stress, a pivotal driver of neurodegenerative diseases, results from an imbalance between the generation of reactive oxygen species (ROS) and cellular antioxidant defenses. This review provides a comprehensive analysis of key oxidative stress sources, focusing on NADPH oxidase (NOX) hyperactivity and mitochondrial Uncoupling Protein (UCP) downregulation. Critically, we examine the therapeutic potential of phytochemicals in mitigating NOX-mediated ROS generation through direct enzyme inhibition, including impacts on NOX subunit assembly and gene expression. Furthermore, we explore the ability of phytochemicals to bolster cellular antioxidant defenses by activating the Kelch-like ECH-associated protein 1 (KEAP1)/nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) signaling pathway, elucidating the upregulation of antioxidant genes, such as GPx, SOD, CAT, and HO-1. This review expands beyond confined overviews; emphasizes specific molecular interactions between phytochemicals and target proteins, including NOX isoforms; and provides an in-depth analysis of the specific antioxidant genes upregulated via Nrf2. This approach aims to pave the way for targeted and translatable therapeutic strategies in neurodegenerative diseases. Ultimately, this review illuminates the intricate molecular dynamics of oxidative stress in neurodegenerative diseases; underscores the potential of phytochemicals to restore redox homeostasis and reverse pathological conditions through precise modulation of key signaling pathways.